THE SOCIAL CONSTRUCTION OF HADITH AUTHORITY: A Comparative Analysis of al-Shafi’is and al-Tusi’s Epistemological Frameworks - Mawarda, Lisa; Arifah, Afro' Anzali Nurizzati; Said, Imam Ghazali; Salim, Moh Fuad; Agatha, Afifah Nurulia (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
This study compares the methodologies for validating āḥādḥadīth according to Imām al-Shāfiʿī (Sunni) and Shaykh al-Ṭūsī (Imāmī Shīʿī). A sociology of knowledge analysis demonstrates that the fundamental differences between the two systems are not merely technical, but rather reflect distinct social contexts and communal needs. The findings show that al-Shāfiʿī formulated universal criteria, such as the integrity (ʿadl) and precision (ḍabṭ) of transmitters, to unify a fragmented Muslim community during the Abbasid era. The system he developed functioned to centralize legal authority based on textual sources, thereby reinforcing Sunni identity as an integrated majority. In contrast, al-Ṭūsī developed a four-tier classification that associates the highest level of authority (ṣaḥīḥ) with Imāmī Shīʿī transmitters, while simultaneously positioning reason (ʿaql) as an independent evaluative filter. Al-Ṭūsī’s system served to maintain identity boundaries, safeguard doctrinal authority, and strengthen internal coherence within a minority community in the post-Occultation period. Both methodologies were subsequently institutionalized through their canonical works such as al-Risālah and al-Kutub al-Arbaʿah, thereby shaping enduring scholarly frameworks that persist until now. This study contributes by uncovering the sociological roots of epistemological differences in ḥadīth studies, demonstrating that religious knowledge authority is shaped by social dynamics such as majority integration and minority preservation. [Penelitian ini mengkomparasikan metodologi validasi hadis āḥād menurut Imam al-Shāfiʿī (Sunni) dan Shaykh al-Ṭūsī (Syiah Imamiyah). Analisis sosiologi pengetahuan menunjukkan bahwa perbedaan mendasar kedua sistem bukan semata teknis, melainkan refleksi dari konteks sosial dan kebutuhan komunal yang berbeda. Hasil menunjukkan bahwa al-Shāfiʿī merumuskan kriteria universal, seperti integritas (‘adl) dan ketelitian (ḍabṭ) periwayat, untuk menyatukan umat Muslim yang terfragmentasi di era Abbasiyah. Sistem yang dikembangkan al-Shafi’i berfungsi memusatkan otoritas hukum berbasis teks, memperkuat identitas Sunni sebagai mayoritas yang terintegrasi. Sebaliknya, al-Ṭūsī mengembangkan klasifikasi empat tingkat yang mengaitkan otoritas tertinggi (ṣaḥīḥ) dengan periwayat Syiah Imamiyah, sekaligus menempatkan nalar (‘aql) sebagai filter mandiri. Sistem yang dikembangkan al-Ṭūsī berfungsi menjaga batas identitas, melindungi otoritas doktrinal, dan memperkuat koherensi internal komunitas minoritas pasca okultasi Imam. Kedua metodologi tersebut kemudian terinstitusionalisasi melalui karya kanonik mereka berupa al-Risālah dan al-Kutub al-Arbaʿah, sehingga membentuk kerangka keilmuan yang bertahan hingga kini. Penelitian ini berkontriusi dengan mengungkap akar sosiologis dari perbedaan epistemologis dalam studi hadis, yakni menunjukkan bahwa otoritas pengetahuan agama dibentuk oleh dinamika sosial seperti integrasi mayoritas dan preservasi minoritas.]